Development of a personalization model for web applications in a context of model-driven development (2017)
ABSTRACT: This dissertation develops and validates a maintainable approach to improve the modifiability of personalized web applications and to reduce the technical complexity to integrate personalization strategies in a short time in a business environment. The Software Reference Architecture to face the maintainability problem was proposed and the MAMPA framework (Model-driven Approach to enhance the Modifiability of Personalized Web Applications) was implemented.